Increased self-immolation frequency and severity during the COVID-19 pandemic. Issue 4 (June 2022) - Jackson, Shane R.; Jung, Mia; Karunaratne, Gehan; Mackenzie, Katherine; Gillies, Rowan; O'Hara, Justine
Abstract: Objective: To determine whether the increased restrictions, isolation and stressors associated with COVID-19 led to an increase in rates or severity of self-immolation burn injuries. Design: Retrospective review of a prospectively-collected database of New South Wales burn patients, comparing 2020 data with the preceding 5 years. Setting: Both adult units in the New South Wales Statewide Burn Injury Service (Concord Repatriation General Hospital and Royal North Shore Hospital). Participants: All adult patients in New South Wales with self-inflicted burn injuries between 1st January 2015 and 31st December 2020. Outcome measures: Demographic information, precipitating factors, burn severity, morbidity and mortality outcomes. Results: We found18 episodes of self-immolation in 2020, compared to an average of 10 per year previously. Burn size significantly increased (43% total body surface area vs 28%) as did revised Baux score (92 vs 77). Most patients had a pre-existing psychiatric illness. Family conflict and acute psychiatric illness were the most common precipitating factors. Conclusion: 2020 saw an increase in both the frequency and severity of self-inflicted burn injuries in New South Wales, with psychiatric illness a major factor. Highlights: There was an increased number of self-immolation presentations to the New South Wales Severe Burn Injury Service in 2020. The mean total body surface area (TBSA) of these burn injuries showed a statistically significant increase from 28% to 43%. Uncertainty, isolation, and reduced access to health services due to COVID-19 may have contributed to these findings.